Multi–dimensional firefly algorithm based on local search for solving unit commitment problem - Yang, Yude; Feng, Yuan; Yang, Lizhen (Frontiers in Energy Research, 2023)
The Unit Commitment problem (UC) is a complicated mixed-integer nonlinear programming problem, so the main challenge faced by many researchers is finding the optimal solution. Therefore, this dissertation proposes a new methodology combining the multi-dimensional firefly algorithm with local search called LS-MFA and utilizes it to solve the UC problem. In addition, adaptive adjustment, tolerance mechanism, and pit-jumping random strategy help to improve the optimal path and simplify the redundant solutions. The experimental work of the optimal unit commitment with the output of 10 machines in a 24-hour period shows that compared with the previous UC artificial intelligence algorithms, the total cost obtained by LA-MFA is less and the result is excellent.